Accountability vital for grads, says Pahang regent - UMP, PNC (The New Straits Times Press (M) Bhd., 2017)
KUANTAN: Time,energy and money invested in educating graduates will be wasted if they fail to make proper decisions for their future, said the Regent of Pahang. Tengku Abdullah Sultan Ahmad Shah said the sacrifies of their family and government would be meaningless if they had a lackadaisical attitude.